Arcana IX: Musicians on Music - Zorn, John 1953- (New York Hips Road, 2021)
Answering a need for critical attention towards experimental and avant-garde music, Arcana is a ground-breaking work --as far-ranging and dynamic as the current generation of musicians. Through manifestoes, scores, interviews, notes and critical papers, performer/composers address composing, playing, improvising, teaching, and thinking in and through music, Rather than an attempt to distill or define musicans' work, Arcana is a remarkable book--challenging and original--essential for composers, musicians, theorists and fans alike.
Keywords: Music criticism